2021
DOI: 10.1002/jso.26375
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of RBM3 expression in surgically treated colorectal lung metastases and paired primary tumors

Abstract: Background The lungs are the second most common site of metastases in colorectal cancer (CRC). The aim of this study was to investigate prognostic factors, including RNA‐binding motif protein 3 (RBM3) expression, in patients with CRC treated with pulmonary metastasectomy (PM). Methods The cohort included all patients treated with PM at Skåne University Hospital, Lund, Sweden, from 2000 to 2014. Clinicopathological, treatment, and survival data were collected. Immunohistochemical staining of RBM3 was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…In the present study, the expression of RBM3 was all over low, which can be conceived as being in line with that expected in mCRC. RBM3 was also found to be heterogeneously expressed and often higher in lymph node or peritoneal metastases than in primary tumours, which is in line with our previous study on colorectal lung metastases 55 . However, and notably, the highest expression was observed in one of the cases with poor prognosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the expression of RBM3 was all over low, which can be conceived as being in line with that expected in mCRC. RBM3 was also found to be heterogeneously expressed and often higher in lymph node or peritoneal metastases than in primary tumours, which is in line with our previous study on colorectal lung metastases 55 . However, and notably, the highest expression was observed in one of the cases with poor prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding RBM3 protein expression, previous studies have reported a largely consistent association between high expression and a favorable outcome, both in cohorts with mixed stages 53 , 54 , and in cohorts with mCRC only 18 , 55 . In the present study, the expression of RBM3 was all over low, which can be conceived as being in line with that expected in mCRC.…”
Section: Discussionmentioning
confidence: 75%
“…Survival in patients after pulmonary metastasectomy for colorectal lung metastases with tumors harboring RAS, BRAF and TP53 mutations were found to be worse than patients with wild type of RAS, BRAF and TP53 gene (48)(49)(50). On the other hand, APC gene and low expression of RNA-binding motif protein 3 expression were associated with better survival after pulmonary metastasectomy (51). Tumor biology appears to play a significant role in the survival of CRC patients with metastatic disease.…”
Section: Indication and Patient Selection Of Pulmonary Metastasectomymentioning
confidence: 89%